1997
DOI: 10.1023/a:1008279503428
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel by three-hour infusion and carboplatin in advanced carcinoma of nasopharynx and other sites of the head and neck

Abstract: The combination of paclitaxel and carboplatin appears to be well tolerated but only moderately active in patients with advanced non-NPC of the head and neck region. However, its activity appears promising in NPC and deserves further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…The response rate in the subset of 35 patients with squamous cell carcinoma was 23%. This is comparable with the activity observed in our study [15]. Similarly, a 39% objective response rate was obtained by Stathopoulos et al [16]among 24 patients treated with paclitaxel 200 mg/m 2 and carboplatin AUC 7.…”
Section: Discussionsupporting
confidence: 93%
“…The response rate in the subset of 35 patients with squamous cell carcinoma was 23%. This is comparable with the activity observed in our study [15]. Similarly, a 39% objective response rate was obtained by Stathopoulos et al [16]among 24 patients treated with paclitaxel 200 mg/m 2 and carboplatin AUC 7.…”
Section: Discussionsupporting
confidence: 93%
“…Dunphy et al, 9 Stathopoulos et al, 14 and Fountzilas et al 8 reported response rates of 54%, 39%, and 23%, respectively. Of note, however, the report by Dunphy et al 9 included patients with newly diagnosed, previously untreated disease and reported a 60% response rate for patients with nasopharyngeal carcinoma, a highly chemotherapy-sensitive malignancy, but only a 23% response rate for other primary SCCHN.…”
Section: Discussionmentioning
confidence: 97%
“…Stathopoulos et al 14 reported 17% incidence of neutropenic fevers. Fountzilas et al 8 reported only 4% incidence of leukopenia and thrombocytopenia and no neutropenic fevers although their study used G-CSF prophylactically on Days 2-12 of each cycle. Hainsworth et al 15 and Shin 16 report 30% and 21% incidence of neutropenic fever, respectively, a rate similar to that in this report, yet Stathopoulos et al 14 suggest that a third agent may be added with little additional myelotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regimen used in this study was effective at a relative minor cost in terms of toxicity, which should be kept as low as possible in the palliative setting. In particular, Dunphy et al [27], Fountzilas et al [28] and Clark et al [29] reported response rates of 54%, 23% and 27%, respectively, but their series also included chemotherapy-naïve patients and higher doses of carboplatin and paclitaxel. Given these important differences, we reached similar response rates and even superior OS in pretreated patients using lower doses of drugs.…”
Section: Discussionmentioning
confidence: 99%